LANNEA DISCOLOR: ITS BOTANY, ETHNOMEDICINAL USES, PHYTOCHEMISTRY, AND PHARMACOLOGICAL PROPERTIES - Maroyi, Alfred (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Lannea discolor is an important component of the traditional, complementary, and alternative medicine health-care systems in several countries. This study is aimed at reviewing the botany, ethnomedicinal uses, phytochemical and biological activities of L. discolor. Information on its botany, medicinal uses, chemistry and pharmacological properties was undertaken using electronic databases such as Pubmed, SCOPUS, Medline, SciFinder, ScienceDirect, Google Scholar, EThOS, ProQuest, OATD and Open-thesis. Pre-electronic literature was sourced from the University Library. The species is used as herbal medicine for 24 human diseases. The major diseases and ailments treated using concoctions prepared from L. discolor include gastrointestinal problems, gonorrhea, infertility in women, convulsions, dizziness, injury, and wounds. Different aqueous and organic extracts of L. discolor exhibited anthelmintic, antibacterial, antimycobacterial, antifungal, antioxidant, antiplasmodial, and nematicidal activities. Detailed studies on the phytochemistry, pharmacological, and toxicological properties of L. discolor are required to correlate the medicinal uses of the species with its phytochemistry and pharmacological properties.